Effects of a urinary trypsin inhibitor on acute circulatory insufficiency after surgical operation - Tani, Tohru; Abe, Hajime; Endo, Yoshihiro; Hanasawa, Kazuyoshi (Am J Surg, 1998)
To assess the effectiveness of an urinary trypsin inhibitor (UTI) on a surgical stress, particularly the influences on cytokines and diuretic hormones. Sixteen patients with carcinoma of the digestive system and predicted to suffer from circulatory insufficiency were enrolled. Selection of group was divided alternatively. UTI was administered for 5 consecutive days, at a dose of 300,000 units per day. Urine and blood specimens were collected before, immediately after, and 1, 3, and 5 days after surgery. Interleukin 8 (IL-8), polymorphonuclear leukocyte elastase (PMNE), vasopressin (ADH), atrial natriuretic peptide (ANP), angiotensin II (AT-II), and endothelin 1 (ET-1) in the blood, and N-acetyl-D-glucosaminidase (NAG) in the urine, were determined. A UTI group was 9 patients, and a control group was 7 patients. The operation time was significantly longer in the UTI group than in the control group. In the UTI group, the elevation of IL-8, PMNE/WBC, ADH, urinary NAG, and BUN were significantly inhibited. AT-II and ET-1, in the UTI group, tended to be suppressed, and ANP showed the similar changes in the two groups. UTI is considered effective in the prevention of excessive reaction against major surgery.